Modulation of Glycolysis and the Pentose Phosphate Pathway Influences Porcine Oocyte In Vitro Maturation. Issue 4 (29th November 2012) - Alvarez, GM; Ferretti, EL; Gutnisky, C; Dalvit, GC; Cetica, PD
Contents: Glycolytic and pentose phosphate pathway (PPP) activities were modulated in porcine cumulus–oocyte complexes (COCs) during in vitro maturation (IVM) by the addition of inhibitors or stimulators of key enzymes of the pathways to elucidate their relative participation in oocyte maturation. The activities of glycolysis and PPP were evaluated by lactate production per COC and by the brilliant cresyl blue test, respectively. Glucose uptake per COC and the oocyte maturation rate were also evaluated. Lactate production, glucose uptake and the percentage of oocytes reaching metaphase II decreased in a dose‐dependent manner in the presence of the pharmacological (NaF) or the physiological (ATP) inhibitors of glycolysis (p < 0.05). The addition of the physiological stimulator of glycolysis (AMP) caused no effect on lactate production, glucose uptake or the meiotic maturation rate. The pharmacological (6‐AN) and the physiological (NADPH) inhibitors of PPP induced a dose‐dependent decrease in the percentage of oocytes with high PPP activity and in the nuclear maturation rate (p < 0.05). The physiological stimulator of PPP (NADP) caused no effect on the percentage of oocytes with high PPP activity. The glycolytic and PPP activities of porcine COCs and maturational competence of oocytes seem to be closely related events. This study shows for the first time the regulatory effect of ATP and NADPH as physiological inhibitors of glycolysis and PPP in porcine COCs, respectively. Besides, these pathways seem to reach their maximum activities in porcine COCs during IVM because no further increases were achieved by the presence of AMP or NADP.